Attaining high magnetic performance in as-sintered multi-main-phase Nd-La-Ce-Fe-B magnets: Toward skipping the post-sinter annealing treatment. (1st May 2019) - Jin, Jiaying; Yan, Mi; Liu, Yongsheng; Peng, Baixing; Bai, Guohua
Abstract: Two-step post-sinter annealing (PSA) treatment, due to its universal applicability, has been one of the most effective strategies for enhancing the coercivity of Nd-Fe-B sintered magnets. Here we report a peculiar phenomenon that the as-sintered multi-main-phase (MMP) Nd-La-Ce-Fe-B magnet exhibits the highest reported to date coercivity of 13.0 kOe upon 25 wt% La-Ce substituting for Nd, combined with B r  = 13.12 kG, and ( BH )max  = 41.67 MGOe. Further annealing cannot enhance the coercivity whereas the remanence and energy product are drastically lowered, i.e. to 11.0 kOe, 12.57 kG, and 38.71 MGOe after two-step PSA, being remarkably different from the conventional Nd-Fe-B. Microstructural analysis reveals that the as-sintered Nd-La-Ce-Fe-B magnet with coexisting REFe2 ( Fd 3 ¯ m ) and RE-rich ( Fm 3 ¯ m ) intergranular phases possesses continuous GB layer isolating adjacent ferromagnetic grains. Hence the beneficial role of PSA on modifying the microstructure and strengthening the coercivity is tiny. Additionally, high-temperature PSA destroys the initial chemical heterogeneity of MMP magnets, leading to the formation of REs homogeneously distributed grains and resultant reduction of the intrinsic magnetic properties. As evidenced by in-situ Lorentz TEM characterization, PSA sample with reduced chemical gradient exhibits quick domain wall motion, compared to the as-sintered one with basically unchanged magnetic domain structure upon the same applied field. The proof-of-principle micromagnetic simulation further confirms that retaining the inhomogeneous La/Ce/Nd distribution is essential to suppress the magnetic dilution effect. These findings demonstrate the realistic prospect of skipping PSA treatment in MMP magnets, which can not only reduce the production process and cost, but also delight the scenario for designing high-performance 2:14:1-type sintered magnets based on abundant La/Ce. Graphical abstract: The as-sintered MMP magnet exhibits a highest reported to date coercivity of 13.0 kOe at 25 wt% La-Ce substitution level, with strengthened remanence of 13.12 kG, and maximum energy product of 41.67 MGOe (a-b). The preferable magnetic performances are attributed to two main features, first is the coexisting REFe2 ( Fd 3 ¯ m ) and RE-rich ( Fm 3 ¯ m ) intergranular phases to form continuous GB layer, as evidenced by the smooth and clear interface between RE2 Fe14 B/RE2 Fe14 B, RE2 Fe14 B/REFe2, and RE2 Fe14 B/fcc-REOx phases (c), second is the retained chemical gradient to form core-shell morphology within an individual grain and intergrain REs deviations (d). The former feature weakens the intergranular exchange coupling, and the latter strengthens the intrinsic magnetic properties, as revealed by the reverse magnetic domain structure across the GB layer and the stable domain walls upon the applied field (e). Image 1